Time‐Dependent Deformations of Sandstone During Pore Fluid Pressure Oscillations: Implications for Natural and Induced Seismicity. Issue 1 (25th January 2019) - Noël, C.; Pimienta, L.; Violay, M.
Abstract: In tectonically active regions, natural seismicity is often correlated with the seasonal hydrology, suggesting that cyclic loading variations might trigger seismicity. Moreover, recent field observations suggest that cyclic fluid injection strategies into geological reservoirs could produce less seismicity than monotonic injections. Here we present 10 brittle creep laboratory triaxial experiments that bring new constraints on fluid‐rock interactions during cyclic pore fluid variations. The experiments were performed on Fontainebleau sandstone with various pore fluid pressure conditions: (i) with constant pore fluid pressure levels from 1 to 10 MPa, at constant Terzaghi effective pressure ( P c − P f = 30 MPa); and (ii) with cyclic (sinusoidal) pore fluid pressure oscillations of varying amplitudes (from 0 to 8 MPa) and periods (from 30 to 3, 000 s) around a mean value of 5 MPa. During deformation, the rock's mechanical properties and the high‐frequency acoustic emission signals were monitored to investigate the physics underlying the rupture processes. Under macroscopically drained conditions, rather than their amplitude, the period of the oscillations appeared to strongly affect the rock sample strength, time‐to‐failure, and dilatancy behavior. Moreover, even for small variations of pore fluid amplitude, and at all pore fluid pressure period, pore fluid pressure and acoustic emissions were strongly correlated. Our experiments demonstrate that pore fluid pressure oscillations may strongly affect rocks mechanical behavior and associated seismic activity. Key Points: Laboratory investigation of the effect of pore fluid pressure oscillations on the creep behavior of Fontainebleau sandstone At low oscillating periods, the amplitude does not affect the strength and deformation rate but these change dramatically at larger periods Acoustic emissions and dilation rates strongly depend on pore fluid pressure oscillations, but dilatancy at failure is constant